The broad-spectrum activity of perampanel: state of the art and future perspective of AMPA antagonism beyond epilepsy - Perversi, Fabio; Costa, Cinzia; Labate, Angelo; Lattanzi, Simona; Liguori, Claudio; Maschio, Marta; Meletti, Stefano; Nobili, Lino; Operto, Francesca Felicia; Romigi, Andrea; Russo, Emilio; Di Bonaventura, Carlo (Frontiers in Neurology, 2023)
Glutamate is the brain's main excitatory neurotransmitter. Glutamatergic neurons primarily compose basic neuronal networks, especially in the cortex. An imbalance of excitatory and inhibitory activities may result in epilepsy or other neurological and psychiatric conditions. Among glutamate receptors, AMPA receptors are the predominant mediator of glutamate-induced excitatory neurotransmission and dictate synaptic efficiency and plasticity by their numbers and/or properties. Therefore, they appear to be a major drug target for modulating several brain functions. Perampanel (PER) is a highly selective, noncompetitive AMPA antagonist approved in several countries worldwide for treating different types of seizures in various epileptic conditions. However, recent data show that PER has the potential to address many other conditions within epilepsy and beyond. From this perspective, this review aims to examine the new preclinical and clinical studies – especially those produced from 2017 onwards – on AMPA antagonism and PER in conditions such as mesial temporal lobe epilepsy, idiopathic and genetic generalized epilepsy, brain tumor-related epilepsy, status epilepticus, rare epileptic syndromes, stroke, sleep, epilepsy-related migraine, cognitive impairment, autism, dementia, and other neurodegenerative diseases, as well as provide suggestions on future research agenda aimed at probing the possibility of treating these conditions with PER and/or other AMPA receptor antagonists.